Marketability of Mango-based Products: Input to Product Development of Locally Farm Produced Mangoes in Central Luzon, Philippines - Jorge, Leslie; Paguia, Hermogenes; Realce, Imelda (JPAIR Multidisciplinary Research, 2020)
Mangifera Indica, commonly known as mango, is a high-value crop with yield gaps brought by its seasonal production. The study was conducted to determine the marketability of mango-based products as one of the most abundant commodities in the Philippines. The study made used a descriptive survey method to describe the type of consumer market and determine their preferences in fruit-based food items. The study revealed that the market consists of varied generations, with the majority under generation Y or the millennials. Most of them were female, single, college graduates, employed, preferred to purchase fruit-based products weekly, and answered that they would be willing to try mango-based products. The market likewise considers products’ nutritional value that researchers, food technologists, and other food manufacturers must capitalize on incubating new product lines and marketing strategies to employ.